Rethinking capital regulation: The case for a dividend prudential target - Manuel A. Mu\~noz (European Central Bank (ECB), 2020)
Recent empirical studies have documented two remarkable patterns shown by euro area banks in the aftermath of the Great Recession: (i) their tendency to boost capital ratios by shrinking assets (contraction of loans supply), and (ii) their reluctance to cut back on dividends (fall in retained earnings). First, I provide evidence of a potential link between these two trends. When shocks hit their pro…ts, banks tend to adjust retained earnings to smooth dividends. This generates bank equity and credit supply volatility. Then I develop a DSGE model that incorporates this mechanism to study the transmission and effects of a novel macroprudential policy rule - that I shall call Dividend Prudential Target (DPT) - aimed at complementing existing capital regulation by tackling this issue. Welfare-maximizing DPTs are effective (more than the CCyB) in smoothing the …financial and the business cycle (by means of less volatile retained earnings) and induce signi…cant welfare gains associated to a Basel III-type of capital regulation through various channels.
Keywords: E44; E61; G21; G28; G35; 330; dividend restrictions; countercyclical capital bu¤ er (CCyB); capital requirements; macroprudential policy; DSGE models